Identification of dipeptidyl peptidase-4 inhibitory compounds of Paederia foetida twigs by nuclear magnetic resonance metabolomics, in silico models, and liquid chromatography–mass spectrometry profiling - Tan, Dai Chuan; Kassim, Nur Kartinee; Ismail, Intan Safinar; Chong, Siok Geok (Chulalongkong University, 2023)
Paederia foetida is a climber that has been traditionally used to treat various diseases, including diabetes. This study aims to investigate the dipeptidyl peptidase-4 (DPP-4) inhibitory activity of P. foetidaI/i> twig extracts and identification of the bioactive compounds by nuclear magnetic resonance (NMR) metabolomics, liquid chromatography–mass spectrometry (LC-MS), and in silico docking study. P. foetida twigs were extracted using organic solvents, namely hexane, chloroform, and methanol and submitted to DPP-4 inhibition assay. Ten milligram of each sample extract was diluted in 700 μL CDCl3 with 0.03% TMS and 1H-NMR spectra were recorded at 25°C on a JEOL FT-NMR spectrometer. The multivariate data analysis, similarity coefficients, and molecular docking study were performed in the study. In vitro assay revealed that the chloroform extract exhibited the highest DPP-4 inhibition (67.40%). The orthogonal partial least square model and LC-MS profiling revealed the presence of 13 metabolites including β-sitosterol, stigmasterol, α-terpineol, scopoletin, rutin, geniposide, apigenin, linarin, lupeol, campesterol, embelin, epifriedelanol, and ursolic acid. In silico molecular docking using the DPP-4 (PDB ID: 1 × 70) crystal structure showed linarin, epifriedelanol, stigmasterol, and ursolic acid (−10.5, −9.3,−9.1, and −8.8 kcal/mol) which were comparable to sitagliptin (−8.8 kcal/mol). This research provided valuable data on the potential biomarker’s antidiabetic inhibitors in P. foetida twigs, suggesting the potential of this plant for the management of diabetes.